(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article analyzes the image of lyrical hero in the light of the realities of post-war reality. Dramatic modus of artistry, novelistic plot-compositional originality, narration, monologic speech allow to describe his feelings and emotions that promote the integrity of the disclosure of this image.